The Effect of Entrepreneurial Orientation and Market Orientation on the Performance of Small and Medium Industries in the City of Banjarmasin - Sulastini Sulastini (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Abstract The development of Micro, Small and Medium Enterprises (MSMEs) in the City of Banjarmasin is quite rapid every year. In running their business, business actors are expected to be able to process existing resources to create added value through various innovations and creative ideas. The development of the Small and Medium Industries has created intense competition and caused entrepreneurs to try to maintain their business. With such intense competition, business actors are required to have an advantage over their competitors. The desire to be superior and to be able to win the competition by applying the right competitive strategy must be possessed by every business actor in order to achieve the expected goals. The aims of this research are (1) to test and analyze Entrepreneurial Orientation on Small and Medium Industry Performance, (2) to test and analyze Market Orientation on Small and Medium Industry Performance. The research method uses descriptive associative survey approach. Data collected through questionnaires, then analyzed using the PLS (Partial Least Square) analysis model using the help of SmartPLS version 3 software. The results of this study are Entrepreneurial Orientation and Market Orientation have a significant effect on the Performance of Small and Medium Industries in the City of Banjarmasin Keywords: Entrepreneurial Orientation, Market Orientation, Small and Medium Industry Performance